2022
DOI: 10.2147/jaa.s335680
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stem Cell-Derived Exosomal miR-301a-3p Regulates Airway Smooth Muscle Cells During Asthma by Targeting STAT3

Abstract: Background Asthma is a chronic inflammatory disease featured by inflammation and remodeling of airway. Adipose-derived mesenchymal stem cell (ADSCs)-derived exosomal miRNAs have been suggested as promising therapeutic manners for diseases. Methods ADSCs and airway smooth muscle cells (ASMCs) were isolated from SD rats. Flow cytometry was conducted to detect the surface biomarkers of isolated cells. Exosomes were extracted by sequentially centrifuge method and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Further functional verification found that miR-16-5p inhibits human ASMC proliferation, whereas miR-30d-5p causes an increase in the average cell diameter of human ASMCs [ 62 ]. F eng et al [ 63 ] found that miR-301a-3p decreases in the blood samples from asthma patients and miR-301a-3p directly targets the 3′-UTR region of STAT3, which suppresses the proliferation and migration of ASMCs, enhances ASMC apoptosis and decreases the inflammatory factor secretions of ASMCs. Similarly, miR-335-5p was found to be underexpressed in the plasma of asthmatic children and further results showed miR-335-5p reduces inflammation, airway fibrosis and autophagy in ASMCs [ 64 ].…”
Section: Mirnas In Asthmatic Asmcsmentioning
confidence: 99%
“…Further functional verification found that miR-16-5p inhibits human ASMC proliferation, whereas miR-30d-5p causes an increase in the average cell diameter of human ASMCs [ 62 ]. F eng et al [ 63 ] found that miR-301a-3p decreases in the blood samples from asthma patients and miR-301a-3p directly targets the 3′-UTR region of STAT3, which suppresses the proliferation and migration of ASMCs, enhances ASMC apoptosis and decreases the inflammatory factor secretions of ASMCs. Similarly, miR-335-5p was found to be underexpressed in the plasma of asthmatic children and further results showed miR-335-5p reduces inflammation, airway fibrosis and autophagy in ASMCs [ 64 ].…”
Section: Mirnas In Asthmatic Asmcsmentioning
confidence: 99%
“…However, they could not differentiate if these effects were associated with exosomes, microvesicles, or a combination of these. In an experiment by Feng et al [ 95 ], the therapeutic potential of AD-MSC-Exo-derived miR-301a-3p was investigated in ovalbumin-induced asthma murine model. They reported that the exosomes were efficiently internalized by airway smooth muscle cells and their secreted miR-301a-3p significantly down-regulated the inflammation, platelet-derived growth factor-BB (PDGF-BB), stimulated proliferation and migration and increased apoptosis in these cells through targeting STAT3.…”
Section: Various Msc-evs In Treatment Of Copd and Asthmamentioning
confidence: 99%
“…(Goetzl et al, 2017) PDGF-BB Exosomal miR-301a-3p derived from adipose-derived mesenchymal stem cellscan lighten remodeling and inflammation of airway smooth muscle cells stimulated by PDGF-BB. (Feng et al, 2022) PDGF-BB Adipose tissue mesenchymal stem cells, bone marrow mesenchymal stem cells, and umbilical cord mesenchymal stem cells secreted exosomes containing PDGF-BB, which can promote keratinocyte and dermal fibroblast proliferation and migration. (Hoang et al, 2020) PDGF-B The exosomes released from astrocytes exerted neurotoxic effects on neurons, which was related to increased miR-29b and decreased PDGF-B expression.…”
Section: Parkinson's Disease Treatment Based On Single-cell Transcrip...mentioning
confidence: 99%